A framework for selection of grid-inverter synchronisation unit: Harmonics, phase-angle and frequency. (October 2017) - Amin, Md. Ruhul; Aizam Zulkifli, Shamsul
Abstract: In this paper, a summary of synchronisation approach which explains about the approach starting from older techniques to advanced computational methods are been discussed. There are many techniques that have been developed focusing on the synchronisation. Generally, in order to evaluate grid parameters, phase-locked-loop (PLL) and later to trigonometric function based on synchronous reference-frame phase-locked-loop, are established on the basis of phase estimation and frequency tracking for grid-inverter connection. The most recent technique, where is the synchronous generator characteristics, has been used in controller strategy at multilevel control programming strategy for distribution of power from the energy sources without the dedicated PLL. In addition to this idea, a concept of synchronous generator for the power processing controller has been developed in order to synchronise the converter with a grid or known as synchronverter can be found.